Time-cost-quality trade-off analysis for construction projects - ElBassuony, Mahmoud (AUC Knowledge Fountain, 2010)
The main objective of construction projects is to finish the project according to an available budget, within a planned schedule, and achieving a pre-specified extent of quality. Therefore, time, cost, and quality are considered the most important attributes of construction projects. The purpose of this study is to incorporate quality into the traditional two-dimensional time-cost trade-off (TCT) in order to develop an advanced three-dimensional time-cost-quality trade-off (TCQT) approach. Time, cost, and quality of construction projects are interrelated and have impacts on each other. It is a challenging task to strike a balance among these three conflicting objectives of construction projects since no one solution can be optimal for the three objectives. The overall performance of a project regarding time, cost, and quality is determined by the duration, cost, and quality of its activities. These attributes of each activity depend on the execution option by which the activity’s work is completed. It is required to develop an approach that is capable of finding an optimal or near optimal set of execution options for the project’s activities in order to minimize the project’s total cost and total duration, while its overall quality is maximized. For the aforementioned purpose, three various Microsoft Excel based TCQT models have been developed as follows: • First, a simplified model is developed with the objective of optimizing the total duration, cost, and quality of simple construction projects utilizing the GA-based Excel add in Evolver. • Second, a stochastic model is developed with the objective of optimizing the total duration, cost, and quality of construction projects applying the PERT approach in order to consider uncertainty associated with the performance of execution options and the whole project. • Third, an advanced multi objective optimization model is developed utilizing a self-developed optimization tool having the following capabilities: 1. Selecting an appropriate execution option for each activity within a considered project to optimize the objectives of time, cost, and quality. 2. Considering the discrete nature of duration, cost, and quality of various options for executing each activity. 3. Applying three various optimization approaches, which are the Goal Programming (GP), the Modified Adaptive Weight Approach (MAWA), and the Non-dominated Sorting Genetic Algorithms (NSGAII). 4. Analyzing both TCT and TCQT problems. 5. Considering finish-to-finish, start-to-start, and start-to-finish dependency relationships in addition to the traditional finish-to-start relationships among activities. 6. Considering any number of successors and predecessors for activities. 7. User-friendly input and output interfaces to be used for large-scale projects. To validate the developed models and demonstrate their efficiency, they were applied to case studies introduced in literature. Results obtained by the developed models demonstrated their effectiveness and efficiency in analyzing both TCT and TCQT problems.